Method of Nonconforming Mixed Finite Element for Second Order Elliptic Problems (Journal of Computational Mathematics, 2000)
In this paper, the method of non-conforming mixed finite element for second order elliptic problems is discussed and a format of real optimal order for the lowest order error estimate.
Keywords: Non-conforming mixed finite element; Error estimate; Second order elliptic problems.